Das Ablautsystem des B- und D-Typs im Harari und Ostgurage - Wagner, Ewald (Aethiopica, 2010)
The verbal system of the East Gurage-Harari-Group inside the southern Ethio-Semitic languages, underwent a special development: The lengthening of the second consonant, the characteristic feature of B-type verbs in the other Semitic languages, totally got lost. The consequence was, that the palatal vowel, which we find already in the Gǝʿǝz imperfect yǝfeṣṣǝm, became the only characteristic of the B-type. It spread over all three verbal forms (perfect, imperfect, jussive) and formed a system of ablaut between ē and ī (and in analogy to that, between ō and ū in the D-type). This however, happened in different ways in the three languages: Silṭe, Harari und Zāy. The article tries to explain how the ablaut systems of the three languages came into being.